Rancang Bangun Sistem Keamanan Kunci Pintu Lemari Berbasis Mikrokontroler - Yoga Adi Saputra; Tata Sutabri (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Cabinet security is generally still done manually and is still done by humans. A common problem that occurs in cabinet security is the ease of dismantling or opening cabinets by irresponsible people until theft of valuable goods or data and very important items occurs. To overcome this, a cabinet security system is needed that can increase the security of goods and data in order to minimize crime. This system is designed using a password door so that it can double the security of the cabinet. This system works when someone wants to open the cabinet door using a password sent via callphone then processed by a microcontroller and displayed by the LCD after using being processed if the password is correct then door will open. The implementation of this system is expected to increase security in cabinets so that they can store important goods or data more safely and the level of security that previously used a manual key is doubled.